PHYSIOTHERAPY MANAGEMENT IN POST-OPERATING RECOVERY OF ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION (ACLR) SINISTRA IN PHASE 1: A CASE REPORT - Jihadilia Islami Putri; Wijianto; Halim Mardianto (JTH: Journal of Technology and Health, 2026)
Anterior cruciate ligament reconstruction (ACLR) requires structured physiotherapy management to support early postoperative recovery. This case report describes phase 1 physiotherapy management and short-term clinical changes in a patient after ACLR. Physiotherapy was conducted in three sessions, with clinical evaluations performed at four time points: T0 as baseline assessment and T1–T3 as follow-up evaluations after each session. The intervention focused on pain management, knee range of motion exercise, muscle activation, and gradual functional training. Outcomes were assessed descriptively using pain intensity, knee range of motion, anthropometric measurement, and the Lysholm Knee Scoring Scale. After physiotherapy, movement pain decreased from 4 to 1, tenderness pain decreased from 5 to 2, and resting pain remained 0. Left knee range of motion improved from S: 10°–10°–65° to S: 5°–10°–75°. Anthropometric measurements showed slight increases at 5 cm, 10 cm, and 15 cm proximal to the tibial tuberosity. Functional ability improved slightly, with the Lysholm Knee Scoring Scale increasing from 44 to 48. These findings indicate short-term clinical improvement during early rehabilitation after ACLR. However, because this study was a single case report with a short intervention period, the results should be interpreted descriptively and cannot be generalized as evidence of intervention effectiveness.